KOMUNIKASI ANTARPRIBADI DALAM MENCEGAH TINDAK KEKERASAN SEKSUAL PADA ANAK - Mutiara Anggraini, (2021)
This study discusses the interpersonal communication of parents and children in preventing acts of sexual violence against children. In relation to data, the number of cases of sexual violence against children has been increasing since the past. This study aims to find out how the intensity of interpersonal communication by parents in preventing sexual violence against children and knowing how openness, empathy, supportive and positive attitudes, and equality of parents are in preventing sexual violence against children. Social Penetration Theory proposed by Irwin Altman and Dalmas Taylor. This research is descriptive qualitative. Data collection techniques were carried out by means of in-depth interviews and observations. The results showed that parents and children have good communication intensity because the frequency of communication is quite high with the quantity of communication as often as possible so that the communication provides benefits for parents and children. The attitude of openness, empathy, supportive and positive attitude, and equality of parents and children in communicating is said to be effective because the communication process continues to develop more intimately, democratically, and harmoniously.